10.1177/1056789514562152 (CrossRef Listing of Deleted DOIs, 2015)
PurposeThis pilot study investigated how retailer training can enhance retailer confidence and participants' shopping experiences to increase WIC benefit redemption.DesignThree groups of retailers were randomized to (1) receive standard training, (2) receive training supplemented with a brief video, and (3) receive no training. Training groups were surveyed before and after training for confidence with WIC-related tasks.SettingWIC-authorized retailer locations in Missouri.Sample44 retailers participated.MeasuresRetailer confidence and total WIC items redeemed before and after training.AnalysisBefore and after training and within and between groups, Pearson's Chi-squared tests compared retailer confidence and analysis of variance and Tukey HSD post-hoc tests compared monthly averages of items redeemed overall and by WIC food category.ResultsConfidence improved for both training groups (standard training: 65% vs 94% (P < 0.00), video: 58% vs 92% (P < 0.00), though the increases in confidence were not different between groups (P = 0.59). Monthly average items redeemed were no different within or between stores or study groups before or after the training.ConclusionsIncreased retailer confidence post-training supports the continued implementation of training and technical assistance. Future programming and research could examine the effects of training on WIC participants' shopping experiences and meeting stocking requirements more specifically.